2015
DOI: 10.1007/s00467-015-3116-4
|View full text |Cite
|
Sign up to set email alerts
|

Podocyte directed therapy of nephrotic syndrome—can we bring the inside out?

Abstract: Several of the drugs currently used for the treatment of glomerular diseases are prescribed for their immunotherapeutic or anti-inflammatory properties, based on the current understanding that glomerular diseases are mediated by immune responses. In recent years our understanding of podocytic signalling pathways and the crucial role of genetic predispositions in the pathology of glomerular diseases has broadened. Delineation of those signalling pathways supports the hypothesis that several of the medications a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 126 publications
1
7
0
2
Order By: Relevance
“…Podocyte loss due to cell death plays a critical role in the development of FSGS 23,24 ; a common histological manifestation of APOL1-associated kidney disease. Upon examining the mechanism of APOL1-induced cytotoxicity, we failed to observe any increase in apoptosis in APOL1 risk allele-transfected cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Podocyte loss due to cell death plays a critical role in the development of FSGS 23,24 ; a common histological manifestation of APOL1-associated kidney disease. Upon examining the mechanism of APOL1-induced cytotoxicity, we failed to observe any increase in apoptosis in APOL1 risk allele-transfected cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This paradigm has been deemed valid for more than 40 years (12). A major conceptual shift from immune-cell mediated to podocyte-mediated diseases occurred by realizing that many inheritable forms of focal segmental glomerulosclerosis (FSGS) are caused by mutations in proteins that are important for podocyte function (reviewed in (13)). Those discoveries provided direct evidence of the essential role of podocytes in the glomerulus, and suggested that direct targeting of the pathogenic pathways within podocytes might have a beneficial effect on glomerular diseases.…”
Section: Do Current Treatments Affect the Actin Cytoskeleton In Podocmentioning
confidence: 99%
“…The addition of converting enzyme inhibitors or angiotensin receptor blockers reduces podocyturia and proteinuria, as they are capable of decreasing podocyte contraction and also reducing the size pores of the glomerular basement membrane and the width of the slit diaphragms. 30 In this respect, despite proteinuria is a useful marker of kidney disease and of glomerular injury, it is not specific of the stage of kidney damage, as it can be found at any stage of chronic kidney disease. Albeit a specific treatment for the disease exists, proteinuria frequently persists, particularly as renal disease worsens.…”
Section: Podocyte Massmentioning
confidence: 99%